الجريمة البيئية دراسة مقارنة - في الفقه الاسلامي والقانون الجزائري - ابي مولود ويداد; بوخلخال صليحة (university of eloued جامعة الوادي, 2025)
نظرا للأهمية الكبيرة التي توليها الجزائر في موضوع الجريمة البيئية وحمايتها أدى بالمشرع الجزائر لإصدار مجموعة من القوانين الخاصة بحماية البيئة، في إطار التنمية المستدامة الذي كان أكثر ملائمة لمسايرة الأحداث والتطورات المعاصرة من حيث المساس بالبيئة كالإعتداء عليها بشتى أنواع الجرئم. ولتحقيق الرّدع العام أوجبت عقوبات لكل مرتكبي تلك الجرائم. ولأنّ أحكام الفقه الإسلامي أكثر نجاعة من القوانين الوضعية. بحثنا في موضوع الجريمة البيئية في الفقه الإسلامي والقانون الجزائري للاستفادة والاستزادة والمقارنة بينهما، متبعين في دراستنا المنهج التحليلي الوصفي والمنهج الاستقرائي، توصلنا إلى مجموعة من النتائج والتوصيات أهمها؛ وقفنا على أن الفقه الإسلامي يضع أسساً أخلاقية وشرعية عامة لحماية البيئة، بينما يركز القانون الجزائري على التفاصيل الإجرائية والعقوبات المحددة، وكلا النظامين يسعى للحد من الجريمة البيئية، لكنهما يختلفان في المنهجية والآليات التنفيذية، مما يبرز أهمية التكامل بين المبادئ الشرعية والتشريعات الحديثة لتحقيق حماية فعالة للبيئة Given the significant importance Algeria attaches to environmental crimes and their prevention, the Algerian legislature has enacted a set of laws specifically aimed at environmental protection. These laws align with sustainable development goals and are designed to address contemporary environmental challenges, including various forms of environmental violations. To achieve general deterrence, penalties have been imposed on perpetrators of such crimes. Since Islamic jurisprudence offers more effective solutions than secular laws, this study examines environmental crimes in both Islamic jurisprudence and Algerian law, aiming to draw comparisons and insights. The research adopts analytical-descriptive and inductive methodologies, leading to key findings and recommendations. Notably, the study reveals that Islamic jurisprudence establishes broad ethical and legal foundations for environmental protection, while Algerian law focuses on procedural details and specific penalties. Both systems aim to combat environmental crimes but differ in methodology and enforcement mechanisms, highlighting the need to integrate Sharia principles with modern legislation for more effective environmental safeguarding.
Keywords: الجريمة البيئة القانون الجزائري Environment Environmental Crime Principles Penalties Environmental Protection